THE NUREMBERG TRIAL AND CONTRIBUTIONS TO THE DEVELOPMENT OF INTERNATIONAL HUMANITARIAN LAW: AN APPRAISAL - ANDREW BUYENGUM JACKSON; GAMBO NELSON (International Studies Journal)
Prior to the Nuremberg trial, war crimes of international magnitude were tried on the state actors. The Versailles Treaty of 1919 which would have brought nation-states to order failed as the result of retribution from the great powers. Closely, the Lieber code of 1863, customary international law, and Briand Kellog pact of 1928 provided a very good playground for international peace and order and it was on this basis that the Nuremberg trial took its shape fostered by Henry Dunant’s book; A Memory of Solferino in 1864. The book codifies international humanitarian law and is a reference for the codes of the military tribunal at Nuremberg for the trial of the Nazi leaders for war crimes against humanity after the Second World War. The paper delves into the study of the Nuremberg trial and its contribution to the development of international humanitarian law at the Geneva Convention. An analytical approach was used as methodology and written sources were consulted.  The findings reveal that the trial enhanced the codification of international humanitarian law by holding responsible individual’s crime under the law in the 1949 Geneva Convention article, the formation of the International Criminal Court, and the Right to Protect. However, the trial was criticized for ethnic cleansing and partiality against the German race. The post-Nuremberg trials of individuals under international humanitarian law provided a new order not only for the law of war but also for medical experimentation and Human Rights which will contribute to the burgeoning literature on   International Humanitarian Law and the law of war.